2010
DOI: 10.1002/we.424
|View full text |Cite
|
Sign up to set email alerts
|

Design of a scaled wind turbine with a smart rotor for dynamic load control experiments

Abstract: The ever increasing size of wind turbines poses a number of design issues for the industry, like increasing component mass and fatigue loads. An interesting concept for reducing fatigue loads is the implementation of spanwise distributed devices to control the aerodynamic loading along the span of the blade, thus mitigating fl uctuations in loading and adding damping to the blade modes. This is usually referred to as the smart rotor concept. In the design of such a rotor, as compared to a traditional one, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…A smart rotor can sense the strain and acceleration which can then be used to control the loading in spanwise direction. The fatigue load reduction potential of a smart rotor was explored by Hulskamp et al [155] experimentally by scaling down the rotor. The results showed that a significant dynamic load and fatigue losses could be reduced if the coupling between the different blades has been taken care of by the controller.…”
Section: Dynamic Load Mitigation On Wind Turbinesmentioning
confidence: 99%
“…A smart rotor can sense the strain and acceleration which can then be used to control the loading in spanwise direction. The fatigue load reduction potential of a smart rotor was explored by Hulskamp et al [155] experimentally by scaling down the rotor. The results showed that a significant dynamic load and fatigue losses could be reduced if the coupling between the different blades has been taken care of by the controller.…”
Section: Dynamic Load Mitigation On Wind Turbinesmentioning
confidence: 99%
“…Aerodynamic and structural details of the blade design can be found in Hulskamp et al (2011). However, as the wind tunnel experiments will also incorporate blade pitch control, the torsional inertia of the blades was reduced by scaling down the root chord by 30 %.…”
Section: Blade Designmentioning
confidence: 99%
“…The dynamic behaviour of the rotor was designed to reflect that of the Upwind 5MW reference turbine [8]. The following equation was used for dynamic scaling [10]:…”
Section: Structural Blade Designmentioning
confidence: 99%
“…In an experimental study, Hulskamp et al [10] designed a two-blade 1.8m diameter rotor that reflects the dynamic behaviour of the Upwind reference [8] turbine using non-dimensional scaling. Strain gages were used to measure the flapwise bending moments.…”
mentioning
confidence: 99%